Tourism Perception of General Toilet Hygiene in Objects and Tourist Attractions in Bali - I Wayan Sunarsa; Nyoma Dini Andiani (Universitas Pendidikan Ganesha, 2019)
This study aims to determine the perception of tourists on the cleanliness of public toilets in Tourist Objects and Attractions in Bali. The population of this study is all public toilets that are spread on the attractiveness of tourism in all districts and cities in Bali. The toilet samples used were 20 public toilets and a sample of 10 respondents from each toilet or equal to 200 people. Data collection methods used are interviews, observations, and questionnaires. Data analysis techniques used are qualitative descriptive and analysis of interest and performance levels. The results showed that tourists' perception of the cleanliness of public toilets on tourist objects and attractions in Bali was 2.18, which meant that the toilets were less clean. Tourist comments show smelly, dirty toilets, no tissue and no soap. The level of suitability between experience and tourist expectations of cleanliness and public toilet facilities at tourist attractions in Bali is 47%. This shows that only 47% of tourist expectations can be met. While the remaining 53% cannot be fulfilled